MONITORING STUDENTS’ RESEARCH WORKS THROUGH AUTOMATED ASSESSMENT SYSTEMS: INNOVATIONS AND PEDAGOGICAL IMPLICATIONS - Rustamova Shokhista Omonjonovna (International Scientific and Current Research Conferences, 2025)
This article examines the emergent role of automated assessment systems in monitoring and evaluating students’ research outputs within contemporary higher education frameworks. It investigates the integration of advanced digital tools and algorithmic evaluation methods that enhance objectivity, reliability, and scalability in academic assessments. The study highlights how these systems contribute to improving research competencies, fostering autonomous learning, and streamlining the assessment process while maintaining rigorous academic standards. Furthermore, it explores the challenges associated with the implementation of automated evaluation, including issues of algorithmic transparency, pedagogical alignment, and ethical considerations in educational contexts.